2012
DOI: 10.1021/ac302450z
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Different Design Alternatives for Microfabricated Nonporous Fused Silica Pillar Columns for Capillary Electrochromatography

Abstract: An experimental study comparing the performance of different designs for microfabricated column structures for microchip capillary electrochromatography is presented. The work is a follow-up to our previously published modeling and simulation study on the same topic. Experiments were performed using fused silica microchips with and without octadecyltrimethoxysilane coating for nonretained and retained modes of operation, respectively. Showing the same trends as the modeling results, the foil shape produces a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 28 publications
0
21
2
Order By: Relevance
“…With these all optimized conditions and methods, such as metal type and morphology, etchant concentration, etching bath change, and ultrasonic treatment, Figure e,h show results for capillary electrochromatography (CEC) pattern fabricated with the present method. The feature widths range from 1.2 mm down to ∼3 μm, due to bifurcating design of the pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these all optimized conditions and methods, such as metal type and morphology, etchant concentration, etching bath change, and ultrasonic treatment, Figure e,h show results for capillary electrochromatography (CEC) pattern fabricated with the present method. The feature widths range from 1.2 mm down to ∼3 μm, due to bifurcating design of the pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it should be noted that the etch depth in Figure 5 c,d is ≈150 µm, showing that the present method can also be applied to the production of thin Si slabs by chemical etching, which might be very useful in Si solar cells (e.g., sliver cell [ 32 ] over large area at a lower cost). With these all optimized conditions and methods, such as metal type and morphology, etchant concentration, etching bath change, and ultrasonic treatment, Figure 5 e,h show results for capillary electrochromatography (CEC) pattern [ 33 ] fabricated with the present method. The feature widths range from 1.2 mm down to ∼3 µm, due to bifurcating design of the pattern.…”
Section: Resultsmentioning
confidence: 99%
“…The exponent n is a variable chosen here to obtain the best fit. The encounter of a negative A value has been recently reported and discussed by Sukas et al for which the authors concluded that forcing the A term to be independent of the linear velocity is an oversimplification that leads to the loss of data [48]. The reduced forms are given as: Table 1.…”
Section: Open-tubular Lcmentioning
confidence: 95%
“…Although the majority of the publications regarding the kinetic plot method relate to RPLC in normal of narrow bore packed bed columns, it has also been applied for chiral analysis [32–35], size‐exclusion chromatography (SEC) [14,36–39], comparison of packed columns with monolithic columns, and optimization of the latter's synthesis [16,40–46], to study the advantages of high temperature LC [47–48], performance of HILIC versus RPLC [49–50], microbore [51–52], open tubular [45,53,54], and pillar array columns [55–59], or to study the effect of the analyte on the kinetic performance limits [60–61]. In these cases, no significant changes to the method are required to establish the kinetic performance limits.…”
Section: Kinetic Plots In Lc (Negligible Mobile Phase Compressibility)mentioning
confidence: 99%
“…For electro‐driven separations, e.g. CEC, the (maximum) pressure can simply be replaced by the (maximum) voltage (ΔV (max) ) and the column permeability can be replaced by the electro‐osmotic flow mobility μ EOF , yielding the following two expressions: [46,54,58–59,67]: N=μEOFΔV()maxHu0andt0=μEOFΔV()maxu02…”
Section: Kinetic Plots In Lc (Negligible Mobile Phase Compressibility)mentioning
confidence: 99%